CHILD GUARDIANSHIP IN INDONESIAN LEGISLATION REGULATIONS - Analiansyah, Analiansyah; Widyanto, Anton; Sam'ani, Sam'ani (Universitas Islam Negeri Ar-Raniry, 2024)
Every child has the fundamental right to protection, which includes having a guardian. If the child's parents are still alive, they are automatically considered the guardians. But in certain cases where this is not possible, a court will assign another person or a governmental institution to act as the child's guardian. The laws and regulations surrounding guardianship in Indonesia are often inconsistent. This study aims to clarify the age requirements for children in need of a guardian, the procedures for appointing a guardian, as well as the duties and responsibilities of guardians according to Indonesian laws. The research also highlights areas for improvement. To achieve this, a statutory approach is adopted, with legal regulations in Indonesia on children and guardianship as the primary source of data. The findings reveal that the age requirements for children to have a guardian range from 16 to 19 years. Additionally, a court order is required for the appointment of a guardian to ensure legal validity. Additionally, the selection of a guardian needs to go through a court ruling in order to ensure legal clarity. The regulations differ from one to another, and in the process, there have been no affirmative efforts taken to expedite the process of appointing a guardian, which has the impact of children not being protected from the start. Affirmation efforts can be carried out through the involvement of village government officials and the subdistrict Religious Affairs Office for those who are Muslim. Then, regarding the duties and responsibilities of guardians, there are still differences either the guardian’s obligation to fulfil a child’s physical and spiritual needs or maintain the child’s assets. These provisions need to be combined to provide comprehensive protection for children from various aspects